2012
DOI: 10.5897/ijps11.893
|View full text |Cite
|
Sign up to set email alerts
|

A study of the surface plasmon absorption band for nanoparticles

Abstract: In this work, we have performed the theoretical calculations of the absorbance of spherical silver nanoparticles dispersed in deionized water and in n-propanol, computed from a summation of the Mie series for different particle radius in the range from 1 to 17 nm. In both solvents, the maximum absorbance increases and the bandwidth at half-maximum absorption and number of particles decrease. Maximum absorbance of silver nanoparticles is higher in n-propanol than in deionized water. These results are due to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…It has been reported that antimicrobial effect was dose dependant. At 0.02 mmol/mL concentration of silver nanoparticles, the 27 mm clear inhibitory zone appeared around 100 μL against S. aureus after incubation for 24 h (Table 1 and Figure 4) followed by C. albicans and S. pneumoniae (25 The in vitro cytotoxic effects of silver nanoparticles were screened against HL-60 cell line and viability of tumor cells was confirmed using MTT assay. The silver nanoparticles were able to reduce viability of the HL-60 cells in a dose-dependent manner as shown in Table 2.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been reported that antimicrobial effect was dose dependant. At 0.02 mmol/mL concentration of silver nanoparticles, the 27 mm clear inhibitory zone appeared around 100 μL against S. aureus after incubation for 24 h (Table 1 and Figure 4) followed by C. albicans and S. pneumoniae (25 The in vitro cytotoxic effects of silver nanoparticles were screened against HL-60 cell line and viability of tumor cells was confirmed using MTT assay. The silver nanoparticles were able to reduce viability of the HL-60 cells in a dose-dependent manner as shown in Table 2.…”
Section: Resultsmentioning
confidence: 97%
“…The result obtained in this investigation is very interesting in terms of the identification of potential forest plants for the synthesis of silver nanoparticles. The frequency and width of the surface plasmon absorption depends on the size and shape of the metal nanoparticles as well as on the dielectric constant of the metal itself and the surrounding medium [24,25] . It is generally recognized that UV-vis spectroscopy could be used to examine size-and shapecontrolled nanoparticles in aqueous suspensions [19,26] .…”
Section: Discussionmentioning
confidence: 99%
“…The UV laser radi ation of the PCQG samples leads to the appearance of plasmon resonance peaks (in the range of λ ~ 350-400 nm), which are intrinsic for quasi metal silver particles [17,[26][27][28]. It follows from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[38] Therefore, the properties of SPR (spectral position and space) can provide valuable information about size, surrounding medium and chemical interaction. [39] The magnitude of SPR also correlates with the presence and absence of p-bond in the dispersing medium. [40] If MNPs' dispersed system is thermally treated, then thermal expansion of copper nanoparticles shows the dominant mechanism of temperature-induced red shift of the SPR.…”
Section: Systemmentioning
confidence: 96%